The plasma kallikrein kinin system in severely ill and traumatised patients. Issue 3 (September 1984) - Cumming, A D; Robertson, C E; Jeffrey, S S; Robson, J S; Ledingham, I M
Abstract : Serial estimations of plasma prekallikrein in four critically ill patients in intensive care showed reduced values in each case, suggesting activation of the plasma kallikrein kinin system. In contrast, samples taken early from 15 patients attending an accident and emergency department with multiple trauma showed significantly elevated plasma prekallikrein concentrations; the significance of this observation is at present unclear.